2012
DOI: 10.5296/ijafr.v2i2.2527
|View full text |Cite
|
Sign up to set email alerts
|

Value relevance of accounting data and financial crisis in Europe: an empirical analysis

Abstract: This paper aims at verifying the relationship between book value and market value for a four years period (2006)(2007)(2008)(2009) in Europe, under IFRS. In particular, I used value relevance approach to measure whether net income or comprehensive income is more useful to understand the relationship between market data and financial data. Moreover, the paper analyzes the impact of financial crisis on the value relevance of accounting data. The examination period runs from a pre-crisis period (2006)(2007) to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
1
1
1
2
Order By: Relevance
“…This suggests that value relevance of accounting figures improved during the financial crisis period. This is in line with the findings of Devalle (2012), who found that the financial crisis had a positive impact on the value relevance of accounting figures prepared under IFRS. However, the coefficient of the financial crisis variable is negative and statistically associated with share prices at a level of 5% when looking at the sub-sample of TC adopting IFRS.…”
Section: Resultssupporting
confidence: 92%
“…This suggests that value relevance of accounting figures improved during the financial crisis period. This is in line with the findings of Devalle (2012), who found that the financial crisis had a positive impact on the value relevance of accounting figures prepared under IFRS. However, the coefficient of the financial crisis variable is negative and statistically associated with share prices at a level of 5% when looking at the sub-sample of TC adopting IFRS.…”
Section: Resultssupporting
confidence: 92%
“…Clarkson et al (2009) used traditional linear pricing model and analyzed whether there was a significant impact on the value relevance of earnings per share and book value per share after IFRS adoption in Australia and Europe and found that accounting information measured under IFRS and local GAAP have the same explanatory power. Contrary to the study of Devalle (2012), who concluded that after IFRS adoption in Germany, the UK, and France, value relevance of earnings per share increased and book value per share increased only in the UK and decreased in other countries. In Belgium, Jermakowicz (2004) analyzed the effects of IFRS on BEL-20 firms and concluded that switching from Belgian GAAP to IFRS resulted in a significant impact on equity as well as net income.…”
Section: Review Of Literaturecontrasting
confidence: 85%
“…Devalle, 2012;Graham et al, 2000) point out that the state of the economy affects value relevance. Devalle (2012) documents that the comprehensive income statement provides more value relevance than the net income provided in the income statement. This conclusion means that the financial recession is positively associated with value relevance.…”
Section: The Proponents Of Fva and The Gfcmentioning
confidence: 99%